Development of a mobile hydraulic press machine using finite element analysis - Widyianto, Agus; Arrozi, Wahyu; Sampurno, Yoga Guntur; Paryanto, Paryanto; Widowati, Asri; Aminatun, Tien; Sunarta, Sunarta (Eastern-European Journal of Enterprise Technologies, 2025)
Mobile hydraulic press machines provide significant benefits in field-based applications such as construction, agriculture, and maintenance, all of which mobility and versatility are of utmost importance. The design and development of mobile hydraulic press machines are responsible for these advantages, which can be attributed to them. The primary focus of this study is to evaluate the structural performance of a mobile hydraulic press machine while it is subjected to operational loads. Formulation, modeling, and simulation of the machine are all carried out with the assistance of finite element analysis (FEA). Cutting-edge computer-aided design (CAD) technologies were applied to develop a model of the machine. This model was then analyzed to ascertain essential parameters such as the distribution of stress, the overall deformation, and the safety aspects. The data imply that the hydraulic telescopic cylinder, press machine frame, waste press, and waste press door all perform within an acceptable safety factor larger than two. In addition, the stress levels are lower than 550 MPa, and the deformation values vary from 0.20 mm to 0.40 mm, significantly lower than the standards for the material. When doing the safety factor analysis, it is essential to locate areas that could benefit from a slight strengthening to enhance the product’s dependability and durability. In addition, the waste press section had an excessively planned safety margin, which indicated room for improvement in material optimization. The structural integrity of the machine is ensured by this all-encompassing approach, which also provides the machine’s efficiency and versatility for various field applications. Future attempts to enhance the concept will focus on prototyping and testing